Macromolecular composite asphalt self-adhesive waterproof coiled material and preparation method thereof

By using polymer composite asphalt self-adhesive waterproof coils, the existing coils have been solved, and the problems of insufficient bonding performance and poor environmental protection in wet and cold environments have been achieved, and high bonding performance and biodegradability in wet and cold environments have been achieved. Low VOC emissions significantly improve mechanical strength and durability, and are suitable for green buildings and environmentally friendly construction.

CN119505732APending Publication Date: 2025-02-25YUNNAN XINCHENG WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411628168.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing waterproof coils have insufficient bonding performance, poor environmental protection and degradability, limited strength and durability, and poor environmental protection in wet and cold environments, making it difficult to meet the needs of modern buildings for multifunctional waterproof materials.

Method used

The self-adhesive waterproof coil of polymer composite asphalt is made of polylactic acid film surface layer, polyurethane matrix, acrylate tackifier and nano-silica, composite asphalt layer of regenerated asphalt and new asphalt, polylactic acid and Environmentally friendly substrates and starch-based degradable isolation films for polyhydroxy fatty acid ester composites.

Benefits of technology

Maintain excellent bonding performance in wet and cold environments, has good biodegradability and low VOC emissions, significantly improves mechanical strength and durability, and meets the requirements of green building and environmentally friendly construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505732A_ABST
    Figure CN119505732A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building waterproof materials, and discloses a polymer composite asphalt self-adhesive waterproof coiled material which comprises a surface layer protective film, a self-adhesive glue layer, a composite asphalt layer, an environment-friendly base material and an isolating film from top to bottom. The surface layer adopts a polylactic acid film, the self-adhesive layer consists of a polyurethane matrix, an acrylate tackifier and nano silicon dioxide, the composite asphalt layer is a mixture of recycled asphalt and new asphalt, an environment-friendly plasticizer is added, and the environment-friendly base material consists of a polylactic acid and polyhydroxyalkanoate composite material. The coiled material disclosed by the invention has excellent adhesive property, durability and environmental protection property, is particularly suitable for the waterproof requirement in a wet and cold environment, can keep stable adhesive force at the temperature of-20 DEG C to 40 DEG C, and has good biodegradability and low VOC (Volatile Organic Compounds) emission. Compared with a traditional waterproof coiled material, the service life is prolonged, the environment-friendly requirement of green buildings is met, and the waterproof coiled material is suitable for building waterproof engineering of roofs, basements, tunnels and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building waterproof materials, in particular to a polymer composite asphalt self-adhesive waterproof coiled material and a preparation method thereof. Background Art

[0002] With the increasing demand for modern building waterproofing projects, the performance requirements of waterproof membranes have gradually evolved from single waterproofing to multifunctionality, including high adhesion, durability, environmental protection, and stability in wet and cold extreme environments. However, existing waterproof membranes have certain technical limitations in structural design and material selection, and cannot fully meet these requirements. Specifically, the shortcomings of existing technologies are mainly manifested in the following aspects:

[0003] Inadequate bonding performance in cold and wet environments

[0004] Traditional waterproofing membranes usually use hot-melt or ordinary asphalt-based self-adhesive layers. These adhesive layers have poor adhesion in environments with temperature changes and high humidity, causing the membrane to easily lose adhesion in low temperature or humid environments. The hot-melt adhesive layer needs to be heated during construction to activate the viscosity, which not only increases the difficulty of construction, but also poses a safety hazard. Ordinary self-adhesive membranes harden at low temperatures and cannot be effectively bonded; in humid environments, their bonding performance will also drop significantly. Therefore, the existing technology is difficult to meet the needs of building waterproofing in cold and humid areas. The bonding performance is unstable under extreme conditions, and problems such as membrane shedding and water seepage are prone to occur, resulting in waterproofing failure.

[0005] Insufficient environmental protection and biodegradability

[0006] With the increasingly stringent environmental regulations and green building standards, the environmental friendliness of waterproofing membranes has gradually become an important concern. However, the materials widely used in existing waterproofing membranes are mostly petroleum-based polymers and non-degradable synthetic materials, which are difficult to degrade in the natural environment. These materials need special treatment after the end of the service life of the membrane, otherwise they will cause long-term pollution to the ecological environment. For example, petroleum-based materials cannot be degraded and are easily accumulated in the soil and water after being discarded, causing adverse effects on the environment. In the context of the development of green buildings, the widespread use of such non-degradable materials limits the application of membranes in environmental protection projects. Therefore, the existing technology has great limitations in the environmental friendliness and degradability of materials, and cannot meet the requirements of sustainable development and green buildings.

[0007] Limited strength and durability

[0008] In actual applications, waterproof membranes need to withstand the long-term effects of various environmental factors such as mechanical stress, high temperature, and ultraviolet rays. However, the composite asphalt layer of existing waterproof membranes is usually based on traditional petroleum-based asphalt, which has weak flexibility and anti-aging properties and is prone to aging, cracking or damage during long-term use. Especially in high-temperature environments, asphalt materials are prone to softening and deformation, resulting in a decrease in the physical properties of the membrane and even loss of the waterproof effect. Although some membranes increase the flexibility of asphalt by adding plasticizers, commonly used plasticizers are mostly phthalate compounds, which not only have potential pollution to the environment, but also migrate under exposure conditions, reducing the plasticizing effect. Therefore, the durability and physical strength of existing waterproof membranes are relatively limited, and cannot fully meet the needs of long-term, high-strength waterproof performance in actual projects.

[0009] High VOC emissions, poor environmental performance during construction

[0010] The self-adhesive layer in traditional waterproofing membranes generally uses solvent-based adhesives or hot-melt materials. These materials will release a large amount of volatile organic compounds (VOCs) during the construction process, posing a potential threat to the health of construction workers and causing pollution to the atmospheric environment. For example, in the construction of hot-melt membranes, the adhesive needs to be activated by heating. This process will be accompanied by the release of more VOCs, which not only increases the difficulty of membrane construction, but also brings environmental pollution problems. Although the construction of self-adhesive membranes using solvent-based adhesives is relatively simple, the volatile VOC content is high, which poses a health hazard to construction workers and does not meet the requirements of green buildings and environmental protection. Therefore, the environmental protection and safety of existing waterproof membranes in construction are poor, and it is difficult to meet the green construction needs of low VOC emissions.

[0011] Therefore, the present invention proposes a polymer composite asphalt self-adhesive waterproofing membrane and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention

[0012] The main purpose of the present invention is to provide a polymer composite asphalt self-adhesive waterproof membrane and a preparation method thereof. The membrane is designed for use in wet and cold environments. It has excellent bonding performance, durability and environmental protection through a high-adhesive self-adhesive layer, a composite environmentally friendly substrate, a durable composite asphalt layer and an environmentally friendly surface layer, thereby overcoming the shortcomings of existing waterproof membranes in terms of adaptability to wet and cold environments, material environmental protection, mechanical strength and construction environmental protection.

[0013] To achieve the above purpose, the present invention is implemented by the following technical scheme: a polymer composite asphalt self-adhesive waterproofing roll, which includes from top to bottom:

[0014] The surface layer is used for the outer protection of the coil, and the material is polylactic acid film with a thickness of 0.03-0.08mm;

[0015] A self-adhesive layer comprising a polyurethane matrix, an acrylate tackifier and nano-silica;

[0016] Composite asphalt layers, which consist of a mixture of recycled asphalt and new asphalt;

[0017] Environmentally friendly substrate, composed of polylactic acid and polyhydroxyalkanoate composite material;

[0018] Isolation film, used to prevent the adhesion of coiled materials, is made of starch-based biodegradable film.

[0019] Preferably, the formula of the self-adhesive layer comprises, by weight percentage: 50-70wt% of polyurethane matrix, 15-25wt% of acrylate tackifier, 3-7wt% of nano-silica, 8-12wt% of isocyanate crosslinking agent, and 3-6wt% of antioxidant.

[0020] Preferably, the formula of the composite asphalt layer includes, by weight percentage: 15-25wt% of recycled asphalt, 8-12wt% of new asphalt, 45-55wt% of polylactic acid, and 15-25wt% of polyhydroxyalkanoate.

[0021] Preferably, the environmentally friendly substrate is a composite film material formed by mixing polylactic acid and polyhydroxyalkanoate in a mass ratio of 4:1 to 6:1.

[0022] Preferably, the nano-silicon dioxide in the self-adhesive layer is surface-modified nano-silicon dioxide, and the particle size is controlled at 10-30 nm, which is used to enhance the adhesion and anti-aging performance.

[0023] Preferably, a method for preparing a polymer composite asphalt self-adhesive waterproof membrane comprises the following steps:

[0024] Preparation of self-adhesive layer: Heat the polyurethane substrate to 70-90°C, add acrylate tackifier, nano-silica, isocyanate crosslinker and antioxidant, stir for 15-30 minutes and then coat and cure;

[0025] Preparation of environmentally friendly substrate and composite asphalt layer: polylactic acid and polyhydroxyalkanoate are mixed in a mass ratio of 4:1 to 6:1, extruded into a film at 180-200°C using a twin-screw extruder, and the composite asphalt layer is coated on the film by a hot pressing process;

[0026] Lamination of the surface layer and the isolation film: The polylactic acid film is covered on the self-adhesive layer by electrostatic adsorption, and then the starch-based isolation film is laminated on the outermost layer of the roll by hot pressing.

[0027] Preferably, in the preparation of the composite asphalt layer, the recycled asphalt and the new asphalt are mixed in a mass ratio of 1.5:1 to 2.5:1, and 3-7wt% of an environmentally friendly plasticizer is added at 170-190°C, and composited with the environmentally friendly substrate through a hot pressing process.

[0028] Preferably, the coating thickness of the self-adhesive layer is 0.5-1 mm, the curing temperature is 55-65° C., and the curing time is 1.5-2.5 hours to ensure the uniformity and stability of the self-adhesive layer.

[0029] Preferably, the thickness of the polylactic acid and polyhydroxyalkanoate substrate is 0.15-0.25 mm, the thickness of the composite asphalt layer is 1-2 mm, the thickness of the water-based self-adhesive layer is 0.2-0.6 mm, and the molding is performed by scraping and hot pressing processes.

[0030] Preferably, the environmentally friendly plasticizer is selected from one or more of citric acid esters, epoxy soybean oil, nonylphenol polyoxyethylene ether or dibutyl phthalate.

[0031] The present invention provides a polymer composite asphalt self-adhesive waterproofing membrane and a preparation method thereof. It has the following beneficial effects:

[0032] 1. The present invention adopts a self-adhesive layer composed of a polyurethane matrix, an acrylate tackifier and nano-silica. By controlling the formula ratio and process parameters, the self-adhesive layer can still maintain excellent bonding performance in a wet and cold environment. In particular, the nano-silica has been surface-modified and the particle size is controlled at 10-30nm, which effectively enhances the cohesion of the adhesive layer and the adhesion to the substrate. Compared with the problem of significantly reduced bonding performance of the hot-melt adhesive layer in low temperature or humid environments in the prior art, the self-adhesive layer of the present invention can still maintain an initial adhesion of more than 1.5N / mm at an ambient temperature of -20°C to 40°C, significantly improving the application performance under cold and humid conditions, and solving the technical deficiencies of the existing coiled materials that are unstable and easy to fall off in extreme environments.

[0033] 2. The environmentally friendly substrate and surface protective film of the coil of the present invention are both formed by a composite of bio-based polymer materials polylactic acid (PLA) and polyhydroxyalkanoate (PHA), and the isolation film is a starch-based degradable film, so that the entire coil has good biodegradability. Through this material design, the present invention can be partially degraded in the natural environment, reducing the long-term pollution of the environment by discarded coils. Compared with the petroleum-based polymer materials widely used in the prior art, which are difficult to degrade and burden the environment, the present invention realizes the environmental transformation of the coil, meets the requirements of green buildings for the environmental protection of materials, and effectively solves the pollution problem in the process of traditional coil waste treatment. At the same time, the addition of PLA and PHA materials ensures that the degradation rate of the coil reaches 30-50% within 3-6 months, providing a sustainable solution for the end-of-life management of the coil.

[0034] 3. The present invention improves the flexibility and crack resistance of the composite asphalt layer by mixing recycled asphalt with new asphalt in a ratio of 1.5:1 to 2.5:1, and adding environmentally friendly plasticizers such as citrate esters and epoxy soybean oil. The composite asphalt is fully combined with the environmentally friendly substrate through a hot pressing process to form a high-strength and high-flexibility composite layer. The coiled material of the present invention has significant tensile strength and aging resistance under environmental conditions such as high temperature, ultraviolet rays, and mechanical friction. Compared with the problem of ordinary asphalt coiled materials in the prior art that are easily softened and deformed at high temperatures or aged due to long-term ultraviolet radiation, the present invention significantly extends the service life of the coiled materials, ensures its stability in exposed environments, and solves the technical deficiencies of traditional coiled materials that are prone to aging and cracking in actual projects.

[0035] 4. The bonding system of the self-adhesive layer of the present invention adopts water-based polyurethane emulsion and rosin-based tackifier, which replaces the traditional solvent-based adhesive and fundamentally reduces the release of VOC. By adopting a low-VOC water-based formula, the coiled material of the present invention greatly reduces the pollution to the environment and the health risks to construction workers during construction and long-term use. Compared with the high VOC emission problem caused by solvent-based adhesives in the prior art, the VOC release of the water-based self-adhesive layer of the present invention at the construction site or in the exposed environment is less than 20μg / m3, which meets the strict requirements of green building and environmental protection standards, effectively solves the problem of traditional coiled materials releasing harmful gases during installation, and provides a safer and healthier construction environment for environmentally friendly construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a flow chart of the preparation method of polymer composite asphalt self-adhesive waterproof membrane. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Please see attached Figure 1 :

[0039] Embodiment 1:

[0040] Recipe composition:

[0041] Self-adhesive layer composition (weight percentage):

[0042] Polyurethane matrix: 60wt%

[0043] Acrylate tackifier: 20wt%

[0044] Nano-silicon dioxide: 5wt%

[0045] Isocyanate crosslinker: 10wt%

[0046] Antioxidant: 5wt%

[0047] Composite asphalt layer composition (weight percentage):

[0048] Recycled asphalt: 20wt%

[0049] New asphalt: 10wt%

[0050] Polylactic acid (PLA): 50wt%

[0051] Polyhydroxyalkanoate (PHA): 20wt%

[0052] Environmentally friendly plasticizer (citrate ester): 5wt%

[0053] Substrate ratio: Polylactic acid (PLA) and polyhydroxyalkanoate (PHA) are mixed in a mass ratio of 5:1. Process steps and parameters:

[0054] Preparation of self-adhesive layer:

[0055] Heat the polyurethane matrix to 80°C, add the acrylate tackifier and nano-silica, and stir at 300 rpm for 20 minutes to ensure uniform mixing.

[0056] Isocyanate crosslinker and antioxidant were added and stirring was continued for 15 minutes.

[0057] The coating thickness was controlled at 0.8 mm and cured at a constant temperature of 60°C for 2 hours.

[0058] Environmentally friendly substrate and composite asphalt layer preparation:

[0059] PLA and PHA were mixed at a mass ratio of 5:1 and extruded into a film at 190° C. in a twin-screw extruder to form a substrate layer with a thickness of 0.2 mm.

[0060] The recycled asphalt and new asphalt were mixed in a ratio of 1.5:1, 5 wt% of a citrate plasticizer was added, and the mixture was hot-pressed and compounded at 170°C to form a composite asphalt layer with a thickness of 1.5 mm.

[0061] Skin layer and barrier film lamination:

[0062] A 0.05 mm thick PLA film is covered on the self-adhesive layer by electrostatic adsorption.

[0063] The starch-based isolation film was laminated on the outermost layer of the coil using a hot pressing device at a pressing temperature of 50°C and a pressure of 5 MPa.

[0064] Summary of embodiments:

[0065] Under this ratio and process conditions, the prepared coil has good adaptability to wet and cold environments, its bonding performance is stable in the range of -20°C to 40°C, and it has good flexibility and environmental performance. The coil has excellent durability and anti-aging performance, and meets the requirements of building waterproofing applications. The parameter selections in this embodiment are all within the recommended range, so the performance of each layer has achieved a good balance, verifying the optimization effect of the present invention within the recommended range.

[0066] Embodiment 2:

[0067] Recipe composition:

[0068] Self-adhesive layer composition (weight percentage):

[0069] Polyurethane matrix: 48wt%

[0070] Acrylate tackifier: 14wt%

[0071] Nano-silicon dioxide: 2wt%

[0072] Isocyanate crosslinker: 7wt%

[0073] Antioxidant: 2wt%

[0074] Composite asphalt layer composition (weight percentage):

[0075] Recycled asphalt: 14wt%

[0076] New asphalt: 7wt%

[0077] Polylactic acid (PLA): 42wt%

[0078] Polyhydroxyalkanoate (PHA): 15wt%

[0079] Environmentally friendly plasticizer (citrate ester): 2wt%

[0080] Substrate ratio: Polylactic acid (PLA) and polyhydroxyalkanoate (PHA) are mixed in a mass ratio of 3:1. Process steps and parameters:

[0081] Preparation of self-adhesive layer:

[0082] The polyurethane matrix was heated to 65°C, and the acrylic tackifier and nano-silica were added and stirred at 250 rpm for 15 minutes.

[0083] Add isocyanate crosslinker and antioxidant and mix for 10 minutes to ensure even distribution of ingredients.

[0084] The coating thickness was controlled at 0.4 mm and cured at 50°C for 1 hour.

[0085] Environmentally friendly substrate and composite asphalt layer preparation:

[0086] PLA and PHA were mixed in a mass ratio of 3:1, and the temperature of the twin-screw extruder was set at 170°C to extrude a substrate with a thickness of 0.1 mm.

[0087] The recycled asphalt and new asphalt were mixed in a ratio of 1.3:1, 2 wt% plasticizer was added, and hot-pressed at 160°C to form a composite asphalt layer with a thickness of 1 mm.

[0088] Skin layer and barrier film lamination:

[0089] A 0.03 mm thick PLA film is covered on the self-adhesive layer and fixed by electrostatic adsorption.

[0090] The starch-based isolation film is hot-pressed and laminated on the outermost layer of the coil, with a pressing temperature of 45°C and a pressure of 4MPa.

[0091] Summary of embodiments:

[0092] When the composition and process parameters are lower than the recommended range, the adhesion of the self-adhesive layer of the coiled material is weakened, the flexibility and aging resistance of the composite asphalt layer are also reduced, and the overall performance of the coiled material shows a large fluctuation, especially the insufficient adhesion in a low temperature environment. In addition, the thickness and strength of the substrate are low, the mechanical support is weak, and the coiled material is prone to cracks in a high stress environment. This example shows that when the composition and process parameters are lower than the recommended range, the performance of the coiled material is significantly reduced, and it is difficult to meet the needs of building waterproofing.

[0093] Embodiment 3:

[0094] Recipe composition:

[0095] Self-adhesive layer composition (weight percentage):

[0096] Polyurethane matrix: 72wt%

[0097] Acrylate tackifier: 27wt%

[0098] Nano-silicon dioxide: 8wt%

[0099] Isocyanate crosslinker: 13wt%

[0100] Antioxidant: 7wt%

[0101] Composite asphalt layer composition (weight percentage):

[0102] Recycled asphalt: 28wt%

[0103] New asphalt: 15wt%

[0104] Polylactic acid (PLA): 57wt%

[0105] Polyhydroxyalkanoate (PHA): 28 wt%

[0106] Environmentally friendly plasticizer (citrate ester): 8wt%

[0107] Substrate ratio: Polylactic acid (PLA) and polyhydroxyalkanoate (PHA) are mixed in a mass ratio of 7:1. Process steps and parameters:

[0108] Preparation of self-adhesive layer:

[0109] The polyurethane matrix was heated to 95°C, and acrylic ester tackifier and nano-silica were added, and the stirring speed was 350 rpm for 30 minutes.

[0110] Add the isocyanate crosslinker and antioxidant and mix for 20 minutes to ensure the ingredients are fully incorporated.

[0111] The coating thickness is 1.2 mm, the curing temperature is 70°C, and the curing time is 3 hours.

[0112] Environmentally friendly substrate and composite asphalt layer preparation:

[0113] PLA and PHA were mixed in a mass ratio of 7:1 and extruded at 210°C to form a film with a substrate thickness of 0.3 mm.

[0114] The recycled asphalt and new asphalt were mixed in a ratio of 2.8:1, 8 wt% of plasticizer was added, and hot-pressed at 200°C to form a composite asphalt layer with a thickness of 2.5 mm.

[0115] Skin layer and barrier film lamination:

[0116] A 0.08 mm thick PLA film was covered on the self-adhesive layer by electrostatic adsorption.

[0117] The starch-based isolation film was laminated on the outermost layer of the coil using a hot pressing device at a pressing temperature of 55°C and a pressure of 6 MPa.

[0118] Summary of embodiments:

[0119] When the composition and process parameters are higher than the recommended range, the overall thickness of the coil increases, resulting in the self-adhesive layer being too thick, the curing time being longer, and the bonding effect being affected. At the same time, the thickness of the composite asphalt layer and the substrate is too high, resulting in a decrease in the flexibility of the coil, making it more difficult to bend and lay during construction. Although the durability has been improved, the overall physical properties of the coil have not been significantly improved. This example shows that the composition and process parameters beyond the range may lead to performance imbalance, reducing the construction adaptability and flexibility of the coil.

[0120] Embodiment 4:

[0121] Recipe composition:

[0122] Self-adhesive layer composition (weight percentage):

[0123] Polyurethane matrix: 55wt%

[0124] Acrylate tackifier: 20wt%

[0125] Nano-silicon dioxide: 6wt%

[0126] Isocyanate crosslinker: 12wt%

[0127] Antioxidant: 7wt%

[0128] Composite asphalt layer composition:

[0129] Recycled asphalt: 18wt%

[0130] New asphalt: 12wt%

[0131] Polylactic acid (PLA): 48wt%

[0132] Polyhydroxyalkanoate (PHA): 22wt%

[0133] Environmentally friendly plasticizer (epoxidized soybean oil): 6wt%

[0134] Substrate ratio: Polylactic acid (PLA) and polyhydroxyalkanoate (PHA) are mixed in a mass ratio of 6:1. Process steps and parameters:

[0135] Preparation of self-adhesive layer:

[0136] Heat the polyurethane matrix to 85°C, add acrylate tackifier and nano-silica, and stir at 300 rpm for 25 minutes.

[0137] Isocyanate crosslinker and antioxidant were added and stirring was continued for 20 minutes.

[0138] The coating thickness is 0.7 mm, the curing temperature is 65°C, and the curing time is 2.5 hours.

[0139] Environmentally friendly substrate and composite asphalt layer preparation:

[0140] PLA and PHA were mixed in a mass ratio of 6:1 at a temperature of 195°C to form a substrate with a thickness of 0.18 mm.

[0141] Recycled asphalt and new asphalt were mixed in a ratio of 2:1, 6wt% epoxy soybean oil was added, and hot-pressed at 190°C for compounding, with a thickness of 1.8mm.

[0142] Skin layer and barrier film lamination:

[0143] The 0.05 mm thick PLA film was covered on the self-adhesive layer using electrostatic adsorption.

[0144] The starch-based isolation film was hot-pressed and laminated at a temperature of 52°C and a pressure of 5 MPa.

[0145] Summary of embodiments:

[0146] This embodiment increases the proportion of nano fillers in the self-adhesive layer, has strong adhesion, and the coil maintains good flexibility and stable bonding effect, which can adapt to various environmental requirements. This example verifies that adding an appropriate amount of nano silicon dioxide can effectively enhance the bonding performance.

[0147] The present invention verifies the influence of the composition of each layer and the process conditions on the performance of the coiled material through the embodiments of different component ratios and process parameters. The experimental results of the five embodiments are summarized below, and the performance of the coiled material in terms of bonding performance, environmental performance, mechanical strength and durability is analyzed through data comparison, with emphasis on the beneficial effects of the present invention in terms of adaptability to wet and cold environments, environmental performance, mechanical strength and construction safety.

[0148] Summary of Example 1:

[0149] In Example 1, all ingredients and process parameters were controlled within the recommended range. The results showed that the prepared coils performed well in terms of adhesion, flexibility, aging resistance and environmental protection. The coils were able to maintain an initial adhesion of 1.5 N / mm in a wet and cold environment of -20°C to 40°C, and no obvious cracks were found in the UV aging test. In terms of environmental protection, the VOCs emissions of the coils were less than 20 μg / m 3The biodegradation rate is more than 40%, which meets the environmental protection requirements of green buildings. The data of this embodiment verifies that the coiled material under the recommended parameters has ideal comprehensive performance, proving the superiority of the technical solution of the present invention.

[0150] Example 2 Summary:

[0151] In Example 2, the composition and process parameters of the self-adhesive layer and the composite asphalt layer are lower than the recommended range. The results show that the adhesion and aging resistance of the coiled material are obviously insufficient. The initial adhesion is only 0.9N / mm at -20°C. The self-adhesive layer hardens under low temperature conditions and the adhesion decreases significantly. The composite asphalt layer is not flexible enough and has low tensile strength, which causes cracks in the coiled material in the ultraviolet aging test. The environmental performance did not meet expectations, and the biodegradation rate dropped to 30%. This example shows that when the composition and process parameters are lower than the recommended range, the mechanical strength and durability of the coiled material are not ideal, and it is difficult to meet the long-term waterproofing requirements in actual projects.

[0152] Example 3 Summary:

[0153] In Example 3, the proportion of each component and the process parameters are all higher than the recommended range. The experimental results show that the overall thickness of the coil is relatively large. Although the bonding performance of the self-adhesive layer is improved, the excessively thick adhesive layer increases the curing time, resulting in incomplete hardening of the internal adhesive layer and difficult construction operations. The excessive thickness of the composite asphalt layer affects the flexibility of the coil, and the coil is prone to curling and breakage under high stress. In the environmental protection test, the VOCs emission was close to 20μg / m 3 , and the biodegradability of the roll material decreased. The results show that when the composition and parameters exceed the recommended range, the roll material is lacking in construction adaptability and environmental friendliness, and cannot achieve a balance in comprehensive performance.

[0154] Example 4 Summary:

[0155] In Example 4, the nano-silicon dioxide content in the self-adhesive layer was appropriately increased, and the process conditions were optimized. The results showed that the adhesion of the coiled material was significantly improved, and the initial adhesion reached 1.6N / mm at low temperatures, and it could remain stable even in wet and cold environments. The composite asphalt layer had good tensile strength and durability, and there was no obvious sign of aging in the UV aging test. The VOCs emission of the coiled material was 15μg / m 3 The biodegradation rate reaches 45%, showing good environmental performance. This example shows that the proper optimization of the self-adhesive layer composition, especially the proportion of nanofillers, can further enhance the bonding performance of the coiled material without affecting the flexibility, verifying the superior effect of the present invention in low-temperature bonding.

[0156] Example 5 Summary:

[0157] In Example 5, the ratio of tackifier and nano-silica was further adjusted to verify its effect on bonding performance and durability. The experimental results showed that the initial adhesion of the self-adhesive layer reached 1.55N / mm, and the flexibility of the coiled material under high and low temperature conditions was excellent. The adhesion of the composite asphalt layer to the substrate was good, and the tensile strength and aging resistance were also effectively guaranteed. In terms of environmental performance, VOCs emissions were controlled at 18μg / m 3 The biodegradation rate of the coiled material is about 42%. This embodiment shows that by adjusting the ratio of the tackifier and the nanofiller, the coiled material achieves a better balance in terms of environmental adaptability and construction safety.

[0158] Data comparison:

[0159]

[0160]

[0161] Summarize:

[0162] By comparing the data of different embodiments, it can be seen that the present invention has the best comprehensive performance under the conditions of ingredients and parameters within the recommended range (Example 1), and can provide excellent adhesion, environmental protection and durability in a wet and cold environment. The embodiment with parameters lower than the recommended parameters (Example 2) showed significant deficiencies in adhesion and durability; the parameters higher than the recommended range (Example 3) resulted in thick and heavy rolls, insufficient flexibility and poor construction adaptability. By optimizing the composition of the self-adhesive layer (Example 4) and the ratio of tackifier and nanofiller (Example 5), the roll showed a more balanced effect in low-temperature adhesion, durability and environmental protection, which further verified the adaptability of the present invention under different environments and requirements, and highlighted the important advantages of the present invention in the application of waterproof rolls in wet and cold environments.

[0163] Comparative experiment:

[0164] Experiment 1: Comparison of adaptability to wet and cold environments

[0165] Purpose:

[0166] The purpose of this experiment is to test the adhesion of different coils in low temperature and high humidity environments, and to verify the adhesion stability and adaptability of the coil of the present invention in extreme wet and cold environments.

[0167] Existing technical solutions:

[0168] Traditional roll material A: Uses traditional asphalt-based self-adhesive layer, relying on the hardening characteristics of the substrate at low temperatures to provide adhesion. The adhesive layer easily loses its stickiness under wet and cold conditions.

[0169] Traditional roll material B: It uses a hot-melt asphalt-based adhesive layer, which requires heating to activate the bonding force. The bonding performance is unstable under wet and cold conditions, and the viscosity decreases significantly at low temperatures.

[0170] Experimental process:

[0171] Sample preparation:

[0172] Samples with a width of 25 mm and a length of 300 mm were cut out from the coil of the present invention, coil A and coil B, and at least 5 copies of each sample were prepared so that repeated testing could improve the accuracy of the results.

[0173] Preprocessing:

[0174] Low temperature and humid cold conditions: The samples were placed in a low temperature cold storage (-20°C, 85% relative humidity) for pretreatment for 24 hours.

[0175] Normal temperature conditions: The samples were pretreated in an environment of 25°C and 60% relative humidity for 24 hours.

[0176] Adhesion test:

[0177] The adhesion test was performed using the 180° peeling method (ASTM D3330 standard). The force was gradually increased on the testing machine until the peeling was complete, and the adhesion (N / mm) was recorded.

[0178] Experimental data:

[0179] Test conditions Coil of the present invention Traditional waterproof membrane A Traditional waterproof membrane B Low temperature (-20℃, 85% humidity) 1.5N / mm 0.9N / mm 1.0N / mm Normal temperature (25℃, 60% humidity) 1.7N / mm 1.6N / mm 1.5N / mm

[0180] Result analysis:

[0181] Under low temperature and damp cold conditions, the coil of the present invention exhibits an adhesive force of 1.5N / mm, which is much higher than coils A and B, proving its high adhesive performance at low temperatures and suitable for extremely cold and high humidity environments. The adhesive force of traditional coils significantly decreases under low temperature and damp cold conditions. The adhesive force of traditional coil A is insufficient at low temperatures, and the viscosity of coil B decreases, which is prone to adhesive failure. The excellent adhesive force of the present invention in damp cold environments is derived from nano-silica and an optimized tackifier ratio, which maintains stable adhesion under damp cold conditions.

[0182] Experiment 2: Comparison of environmental performance of materials

[0183] Purpose:

[0184] The purpose of this experiment is to compare the biodegradation rates and VOCs releases of different coils and to evaluate the environmental friendliness and potential impact of the coils.

[0185] Existing technical solutions:

[0186] Traditional roll material A: The main component is petroleum-based asphalt, which has low biodegradability and uses phthalate plasticizers, which may release higher VOCs.

[0187] Traditional roll material B: polymer modified asphalt, which improves durability but is non-degradable and has high VOC emissions during the construction process.

[0188] Experimental process:

[0189] Biodegradability Test:

[0190] The samples of the coiled material of the present invention, coiled material A and coiled material B were respectively buried in artificial simulated soil (humidity 60%, temperature 25° C.) for 3 months, the mass loss rate of the samples was recorded every month, and the total degradation rate (%) after 3 months was calculated.

[0191] VOCs emission test:

[0192] The samples were placed in a closed test environment (25°C) and the VOCs release within 24 hours was tested using a gas chromatography-mass spectrometer (GC-MS). The results were expressed in μg / m 3 express.

[0193] Experimental data

[0194] Test items Coil of the present invention Traditional waterproof membrane A Traditional waterproof membrane B Biodegradation rate (3 months) 0.4 0.05 0.1 VOCs emission (24 hours) <![CDATA[15μg / m 3 ]]> <![CDATA[35μg / m 3 ]]> <![CDATA[30μg / m 3 ]]>

[0195] Result analysis:

[0196] The biodegradation rate of the coiled material of the present invention reaches 40% within 3 months, which is higher than 5% of the traditional coiled material A and 10% of the coiled material B, showing good biodegradability, which is due to the environmentally friendly PLA and PHA substrates used in the present invention. At the same time, the VOCs release of the coiled material of the present invention is only 15μg / m 3 , which is much lower than that of traditional coiled materials, indicating that the present invention has significant advantages in environmental protection performance and is suitable for green building applications.

[0197] Experiment 3: Comparison of mechanical strength and construction environmental protection

[0198] Purpose:

[0199] Test the tensile strength, UV aging resistance and VOC emissions of different membranes under construction conditions to verify the environmental protection and mechanical properties of the membranes.

[0200] Existing technical solutions

[0201] Traditional roll material A: Mainly composed of ordinary asphalt composite layer, with low mechanical strength and aging resistance, and high VOC emissions.

[0202] Traditional membrane B: uses modified polymers and petroleum-based plasticizers, has higher tensile strength, but still has higher VOC emissions during construction.

[0203] Experimental process:

[0204] Tensile strength test:

[0205] The tensile strength was tested according to ASTM D412 standard. The sample was gradually stretched to break and the maximum tensile strength (MPa) was recorded.

[0206] UV aging test:

[0207] Place the sample in a UV-B light source accelerated aging box for 500 hours, observe the sample surface regularly, and record whether there are signs of aging such as cracks and discoloration.

[0208] Construction VOC emission test:

[0209] The samples were placed in a heated environment at 60°C (simulating construction conditions) and the total VOC release within 1 hour was recorded to evaluate the impact on the environment and human body during the construction process.

[0210] Experimental data:

[0211] Test items Coil of the present invention Traditional waterproof membrane A Traditional waterproof membrane B Tensile strength(MPa) 6.8 4.3 5 UV aging (500 hours) No cracks Cracks appear Surface aging <![CDATA[Construction VOC Emission (μg / m 3 )]]> 20 70 60

[0212] Result analysis:

[0213] The tensile strength of the coil of the present invention is 6.8MPa, which is significantly higher than that of the traditional coil, indicating that the present invention has superior mechanical strength and can withstand greater stress and remain stable. In the ultraviolet aging test, the coil of the present invention had no obvious cracks after 500 hours, while the traditional coil A had cracks and the surface of coil B was seriously aged. The construction VOC emission test showed that the VOC emission of the coil of the present invention in a heated environment was only 20μg / m 3 , significantly lower than the traditional coil A (70μg / m 3 ) and B (60 μg / m 3 ), indicating that the coiled material of the present invention is suitable for low VOC environmental protection construction requirements.

[0214] Experimental summary:

[0215] The comparative experimental data further verified the significant improvements of the present invention in terms of adaptability to wet and cold environments, environmental friendliness of materials, mechanical strength and environmental friendliness of construction. The following is a summary of the data:

[0216]

[0217] Summary of results:

[0218] Adaptability to wet and cold environments: The bonding strength of the present invention in low-temperature and wet environments is significantly higher than that of traditional rolls, indicating that it can maintain stable bonding strength in extreme environments and is suitable for cold and wet construction conditions.

[0219] Environmental friendliness of materials: The test results of biodegradability and VOCs emission show that the roll material of the present invention has significant advantages in biodegradability and low VOC emission, meets the environmental protection requirements of green buildings, and is suitable for the environmental protection needs of modern buildings.

[0220] Mechanical strength and durability: In the tensile strength and ultraviolet aging tests, the coiled material of the present invention performs excellently, indicating that it has excellent durability and anti-aging properties under extreme climatic conditions and is suitable for projects with high-strength waterproofing requirements.

[0221] Environmental protection during construction: The VOC emission of the coiled material of the present invention is much lower than that of traditional coiled materials, which greatly reduces the release of harmful gases during the construction process and provides a more environmentally friendly and healthy construction environment for construction workers.

[0222] In summary, the polymer composite asphalt self-adhesive waterproof membrane of the present invention performs excellently in adaptability to wet and cold environments, environmental performance, mechanical strength and construction environmental protection, is significantly superior to traditional waterproof membranes, and has broad application prospects.

[0223] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A polymer composite asphalt self-adhesive waterproof roll, characterized in that: The roll includes from top to bottom: The surface layer is used for the outer protection of the coil, and the material is polylactic acid film with a thickness of 0.03-0.08mm; A self-adhesive layer comprising a polyurethane matrix, an acrylate tackifier and nano-silica; Composite asphalt layers, which consist of a mixture of recycled asphalt and new asphalt; Environmentally friendly substrate, composed of polylactic acid and polyhydroxyalkanoate composite material; Isolation film, used to prevent the adhesion of coiled materials, is made of starch-based biodegradable film.

2. The polymer composite asphalt self-adhesive waterproofing membrane according to claim 1, characterized in that: The formula of the self-adhesive layer includes, by weight percentage: 50-70wt% of polyurethane matrix, 15-25wt% of acrylate tackifier, 3-7wt% of nano silicon dioxide, 8-12wt% of isocyanate crosslinking agent, and 3-6wt% of antioxidant.

3. The polymer composite asphalt self-adhesive waterproofing membrane according to claim 1, characterized in that: The formula of the composite asphalt layer includes, by weight percentage: 15-25wt% of recycled asphalt, 8-12wt% of new asphalt, 45-55wt% of polylactic acid, and 15-25wt% of polyhydroxyalkanoate.

4. The polymer composite asphalt self-adhesive waterproofing membrane according to claim 1, characterized in that: The environmentally friendly substrate is a composite film material formed by mixing polylactic acid and polyhydroxyalkanoate in a mass ratio of 4:1 to 6:

1.

5. The polymer composite asphalt self-adhesive waterproof membrane according to claim 1, characterized in that: The nano silicon dioxide in the self-adhesive layer is surface-modified nano silicon dioxide, and the particle size is controlled at 10-30 nm.

6. A method for preparing the polymer composite asphalt self-adhesive waterproof membrane according to any one of claims 1 to 5, comprising the following steps: Preparation of self-adhesive layer: Heat the polyurethane substrate to 70-90°C, add acrylate tackifier, nano-silica, isocyanate crosslinker and antioxidant, stir for 15-30 minutes and then coat and cure; Preparation of environmentally friendly substrate and composite asphalt layer: polylactic acid and polyhydroxyalkanoate are mixed in a mass ratio of 4:1 to 6:1, extruded into a film at 180-200°C using a twin-screw extruder, and the composite asphalt layer is coated on the film by a hot pressing process; Lamination of the surface layer and the isolation film: The polylactic acid film is covered on the self-adhesive layer by electrostatic adsorption, and then the starch-based isolation film is laminated on the outermost layer of the roll by hot pressing.

7. The method for preparing a polymer composite asphalt self-adhesive waterproofing membrane according to claim 6, characterized in that: In the preparation of the composite asphalt layer, the recycled asphalt and the new asphalt are mixed in a mass ratio of 1.5:1 to 2.5:1, and 3-7wt% of an environmentally friendly plasticizer is added at 170-190°C, and the composite asphalt is compounded with the environmentally friendly substrate through a hot pressing process.

8. The method for preparing a polymer composite asphalt self-adhesive waterproofing membrane according to claim 6, characterized in that: The coating thickness of the self-adhesive layer is 0.5-1 mm, the curing temperature is 55-65° C., and the curing time is 1.5-2.5 hours.

9. The method for preparing a polymer composite asphalt self-adhesive waterproofing membrane according to claim 6, characterized in that: The thickness of the polylactic acid and polyhydroxyalkanoate substrate is 0.15-0.25 mm, the thickness of the composite asphalt layer is 1-2 mm, and the thickness of the water-based self-adhesive layer is 0.2-0.6 mm. The process is formed by scraping and hot pressing.

10. The method for preparing a polymer composite asphalt self-adhesive waterproofing membrane according to claim 7, characterized in that: The environmentally friendly plasticizer is selected from one or more of citric acid esters, epoxy soybean oil, nonylphenol polyoxyethylene ether or dibutyl phthalate.